O processo de referenciação na leitura de crônicas - Santos, Viviane Dias dos (2010)
This dissertation is in the field of reading, writing and portuguese language teaching whose topic is the study of chronicle reading referentiation process. From the idea that the referentiation process may be constituted as strategies which collaborate with the reading comprehension and with an independent and critical reader education, the objective is to check how the referentiation strategies are built up and assure the textual development as well as point out the text clincher orientation. For this, the research fundamentals are found in studies of reading and reading comprehension strategies by Van Dijk (2004), Koch (1997, 2004, 2008a, 2008b, 2009), Koch & Elias (2008, 2009), Marcuschi (1985, 2004, 2007, 2008); of referentiation according to Mondada & Dubois (2003), Mondada (2005), Apothéloz (2003), Conte (2003), Francis (2003), Cavalcante (2003), Marcuschi (2000, 2005), Koch & Marcuschi (1998), Koch ( 1997, 2004, 2007a, 2007b, 2008a, 2008b, 2009), Adam (2008), Marquesi (2007a, 2007b) and Marquesi & Elias (2008). The analyses bring into the open that the referentiation helps the reader in sense building, once this process points out the clincher orientation as well as the rebuilding of the discursive objects. So, the referential process may contribute to the proficient readers education